Real-time performance monitoring of microwave line-of-sight links in mobile communication using fiber Bragg grating sensors for vibration and acceleration detection at mobile base stations - Ozturk, Ibrahim; Unverdi, N. Ozlem (ELSEVIER SCIENCE INC, 2026)
This study presents a real-time performance monitoring approach for microwave line-of-sight links in mobile base stations, utilizing triaxial fiber Bragg grating (FBG) accelerometers to detect and analyze vibration- and acceleration-induced disturbances that affect the radio link system. A total of seven experimental test scenarios were conducted under controlled external excitations. Key performance indicators, including background block error rate (BBER), errored seconds (ES), errored seconds rate (ESR), severely errored seconds (SES), and severely errored seconds rate (SESR), were analyzed to quantify the effects of mechanical disturbances on radio link stability. Experimental results show that high-amplitude accelerations cause temporary degradation in channel quality, leading the system to downgrade its modulation scheme from high levels, such as 4096 quadrature amplitude modulation (QAM), to lower levels, like 4 QAM. These degradations were reversible, as modulation levels returned to higher states once channel conditions improved. Additionally, performance degradations were found to be associated with physical factors such as structural contact issues at the radio link pole, external interferences, or wind-induced oscillations. Unlike conventional methods, the proposed system enables remote and real-time detection of environmental mechanical anomalies. This work introduces a novel framework integrating acceleration measurements with link performance metrics, establishing a foundation for predictive maintenance and autonomous fault detection in wireless communication infrastructure.
Keywords: Communication technologies; Optical communications; Mobile communications; Fiber Bragg grating (FBG) sensor; Mobile base station; Fixed wireless links; Performance monitoring; MILLIMETER-WAVE; SYSTEM; WIND; GHZ; Engineering; Optics; Telecommunications